MOTOR VEHICLE ADMINISTRATION APPLICATION FOR SERVICE ON THE WORKSHOP BIMOS MOTOR USING VISUAL BASIC 6.0 - Gunawan Wibisono; Eko Hadiyanto, SSi, MM (Jurnal Sistem Informasi, 2004)
On every bike shop, bike shop would have the data of each customer. Usually, customer data is stored in the form of certain files. These data will be information for consumers, and part information with an interest in these data. There are times when customers will also require such information. Of course, customers will ask what that will be repaired and replaced sparepart. Obviously part of that information will find the information requested by the customer. In such a case, then the information will have difficulty in finding such information. This is because the customer data in the search is still done manually or not computerized and the data is still stored in the form of files. As a result, the search is likely to fail, even if the data is found, it will take a long time. To solve this problem, the authors argue the need for an application to search the customer records. So that the things that are not desired / adverse will not occur.